Making meaning of trauma in psychosis - van Sambeek, Nienke; Franssen, Gaston; van Geelen, Stefan; Scheepers, Floortje (Frontiers in Psychiatry, 2023)
Background: Finding new meaning and identity in the aftermath of trauma has been identified as a key process of mental health recovery. However, research indicates that this meaning-making process is compromised in people with psychosis. Considering the high prevalence, yet under-treatment of trauma in people with psychosis, it is urgent to gain insight into how their meaning-making process can be supported.To gain insight into how people with psychosis make meaning of trauma and identify barriers and facilitators in their meaning-making process.Methods: Qualitative inquiry of N=21 interviews transcripts from the Dutch Psychiatry Storybank. We included interviews of people who a) lived through multiple psychotic episodes, and b) spontaneously addressed traumatic experiences in a low-structured interview. Storyline analysis was performed to gain insight into the meaning-making of trauma within their self-stories. Psychosocial conceptualizations of narrative identity were used to inform the analysis. A data-validation session with four experts-by-experience was organized to check and improve the quality of our analysis.We identified four different story types: (1) Psychiatry as the wrong setting to find meaning;(2) The ongoing struggle to get trauma-therapy; (3) Exposure to trauma as a threat to a stable life, and (4) Disclosure as the key to resolving alienation. Each story type comprises a different plot, meaning of trauma withing the self-story, (lack of) integration and barriers and facilitators in the meaningmaking process. Overall, barriers in the meaning-making process were mostly situated within mental healthcare and stigma-related. People felt particularly hindered by pessimistic ideas on their capacity to develop self-insight and cope with distress, resulting in limited treatment options. Their process of adaptive meaning-making often started with supportive, non-judgmental relationships with individuals or communities that offered them the safety to disclose trauma and motivated them to engage in a process of self-inquiry and growth.The outcomes illuminate the social context of the meaning-making challenges that people with psychosis face and illustrate the devastating influence of stigma. Our outcomes offer guidance to remove barriers to adaptive meaning-making in people with psychosis, and can help clinicians to attune to differences in the meaning-making of trauma.